Pulmonary function test in upper airway obstruction: a simple yet effective diagnostic test - Amit Panjwani; Jaini Lodha (SpringerOpen, 2019)
Upper airway obstruction (UAO) is a dangerous condition that is associated with significant mortality. It is easily diagnosed when its presentation is acute, but subacute or chronic presentation may pose a diagnostic dilemma resulting in disastrous consequences. Clinical evaluation may provide subtle clues towards its presence, whereas pulmonary function test can provide useful information to confirm the presence and site of UAO. Relevant radiological and endoscopic investigation may then be carried out to identify the exact etiology and institute appropriate therapy. We present a case of chronic UAO that was detected with the help of pulmonary function test and confirmed with computed tomography and endoscopy. The etiology was found to be related to fibrosis of the larynx resulting in the immobility of the vocal cords secondary to radiotherapy given to the patient 7 years ago. This is an unusual presentation, as most of the radiotherapy-related fibrosis in the head and neck region present within a few months of the exposure to radiation.